Blended Learning Approach: A Case Study - Redoblo, Cristine (JPAIR Multidisciplinary Research, 2015)
The computer era has come to integrate and assimilate in the academic curriculum and instruction. The Blended Learning adaptation further added to the teaching and learning experience in the classroom. The study investigated the factors on the use of ICT in terms of Computer usage, Internet usage, Multimedia usage and Mobile usage in Blended Learning Approach among the faculty. It analyzed the SWOT (strengths, weaknesses, opportunities and threats) of blended learning for a Proposed 5-year Instructional Design Strategic Plan. The study used quantitative research design by the use of the constructed questionnaire and qualitative through the conducted focus group discussions within the four campuses of CHMSC. The study revealed that CHMSC faculty exhibited low extent of use of blended learning. The result also showed a significant difference in the extent of use of ICT in terms of age, sex, and workplace whereas civil status, subject taught, and educational qualification do not significantly differ. The identified factors that affect blended learning were used as a basis for a Proposed Instructional Design Strategic Plan and projected after five years. The development and package of learning materials will be realized to the clients of the institutions and other stakeholders.